Oxidation catalysis by large trisoctahedral gold nanoparticles: Mind the step! - Sreedhala, S.; Sudheeshkumar, V.; Vinod, C. P. (Catalysis Today, 2015)
To understand the origin of catalysis by gold and to probe the role of defects and interfaces, benchmark reactions namely CO oxidation and benzyl alcohol oxidation were carried out on supported trisoctahedral gold nanoparticles and on the inverse catalyst system. The sizes of these particles which are between 45 nm and 110 nm, are well beyond the quantum size regime and well above the optimum size range where gold is considered to be catalytically active. The periodic steps sites in contact with oxide support interface were able to promote the reaction. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: CO oxidation; Defects; Gold catalysis; Inverse catalysta; Steps and kinks

Surfactant assisted formation of ruthenium nanochains under mild conditions and their catalytic CO oxidation activity - Sreedhala, S.; Vinod, C. P. (Chemical Communications, 2015)
Spontaneous formation of ruthenium nanochains is accomplished in aqueous medium under mild conditions using a seed mediated protocol with cetyl trimethylammonium bromide (CTAB) as the capping agent. They are formed due to the random self-assembly of Ru seeds of similar to 3.5 nm size. These 1D nanostructures exhibit better catalytic activity towards the oxidation of CO relative to the similar to 3.5 nmseeds and 6 nm Ru nanospheres. The synthesis strategy adopted here is found to be simple, facile and environmentally friendly.

CO oxidation on large high-index faceted Pd nanostructures - Sreedhala, S.; Sudheeshkumar, V.; Vinod, C. P. (Journal of Catalysis, 2016)
The structure sensitivity of CO oxidation has been investigated on oxide-supported palladium nanoparticles of different morphologies. The reactivity of concave nanocubes and nanoflowers that expose {3 1 0} and {3 1 1} high-index facets showed a lower onset temperature for CO oxidation than Pd nanospheres of size around 6 nm. These concave nanocubes and nanoflowers were also found to catalyze the CO oxidation reaction more efficiently than simple cubes and spheres of similar size that exposed low-index facets. The enhanced activity of these nanoparticles compared with other morphologies are attributed to the presence of sites of under-coordination on the exposed high-index facets. The larger nanoparticles were also found to be more stable in the reaction environment. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: CO oxidation; High-index facets; Pd nanoparticles; structure sensitivity

Large trisoctahedral Au nanoparticles encapsulated inside porous silica catalyses CO oxidation at room temperature: probing the effect of encapsulation and the role of step atoms and interfaces - Sreedhala, S.; Maheshwari, Shruti; Betsy, K. J.; Vinod, C. P. (Applied Catalysis A-General, 2016)
As envisaged, a synthesis strategy is reported for encapsulating high index faceted trisoctahedral Au nanoparticles inside porous silica to preserve nanoparticle size by preventing sintering. Further, to probe the role of interfaces an active metal oxide junction was created by decorating trisoctahedral (TOH) Au nanoparticle with nano oxides before silica encapsulation. The activity of these catalysts was tested for CO oxidation reaction. The reaction was found to be facile on these encapsulated large structured Au nanoparticles showing appreciable activity at room temperature compared to non encapsulated counterparts. Apart from preventing sintering, the improved activity is demonstrated due to the retention of morphology and thereby the active centres due to encapsulation. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Defect sites; Encapsulation; High index facets; Metal-oxide active perimeter; Trisoctahedral Au nanoparticles

Model nanoparticles in catalysis - Vinod, C. P.; Vysakh, A. B.; Sreedhala, S. (Metal nanoparticles and clusters: advances in synthesis, properties and applications, 2017)
The importance of surface structure in catalysis is well documented by a large volume of surface science studies carried out on single crystal surfaces. Recent years has seen rapid strides in the synthesis of structured nanomaterials with varying morphologies and architecture. There is a growing interest in utilizing model nanoparticles like morphology-controlled nanostructures and core–shell-like bimetallic nanoparticles in catalysis. Apart from showing unprecedented reactivity, they serve as a model surfaces to answer many fundamental question in catalysis and also to arrive at structure vs activity correlations in heterogeneous catalysis. This chapter gives an introduction to such nanomaterials and recent advances in utilizing these materials for catalytic applications.

Mechanistic insights into the pathways of phenol hydrogenation on Pd nanostructures - Porwa, Govind; Gupta, Shelaka; Sreedhala, S.; Elizabeth, Joes; Ithan, Tuhin Suvra; Haider, M. Ali; Vinod, C. P. (ACS Sustainable Chemistry & Engineering, 2019)
Product selectivity in aqueous phase phenol hydrogenation on well-defined supported Pd nanostructures (spheres, cubes, and octahedra) was studied using defined experiments and density functional theory (DFT) simulations. On Pd spheres and octahedra, the reaction initially showed high selectivity (in the first 3 h, at 363 K and 5 bar H-2 pressure) toward the partially hydrogenated product cyclohexanone. On prolonged operation (>20 h of reaction time), a shift in the product selectivity (up to 100%) toward the completely hydrogenated product cyclohexanol was observed on Pd spheres and octahedra. In contrast, the reaction on Pd cubes, which only had {100} facets, showed a high selectivity (similar to 90%) toward the product cyclohexanone even after 40 h, at the same reaction conditions. Since the {111} facets are expected to be the majority sites on a spherical particle, we attribute the selectivity trend observed on spherical Pd particles to be primarily controlled by the selectivity trend on the Pd{111} facets. This observation was further confirmed on performing the hydrogenation reaction on a mixture of Pd cube and Pd octahedron particles in a ratio of 25:75 (representing the site ratio of a spherical particle). DFT simulations provided a mechanistic insight into the reactivity of the two different facets ({100} and {111}) toward phenol hydrogenation. The calculations revealed that the selectivity significantly depended on the activation barriers involved in cyclohexanone hydrogenation on the Pd{111} facets (77 and 57 kJ/mol) as compared to those on the Pd{100} facets (97 and 101 kJ/mol).
Keywords: Cyclohexanol; cyclohexanone; facet-dependent reactivity; phenol hydrogenation